Inclusive Early Childhood Education, Play and Recreational Activities as Predictors of Social Adjustment of Children with Hearing Impairment in Oyo State, Nigeria - Uko, Francesca (e-Pedagogium, 2018)
This study investigated inclusive early childhood education, play and recreational activities as predictors of social adjustment of children with hearing impairment in Oyo State, Nigeria. A sample of two hundred and seventy (270) participants comprising of 150 teachers having children with hearing impairment in their classrooms and 120 parents of children with hearing impairment. A ten (30) item questionnaire with a 4-point rating scale and reliability coefficient of 0.71 to 0.77 was used to collect teachers' and parents' opinions on inclusive early childhood education, play and recreational activities as predictors of social adjustment of children with hearing impairment. The data collected were statistically analyzed using Pearson Product Moment Correlation and was used to determine the significant relationship in the stated research questions while Multiple Regression Analysis (MRA) was used to verify whether the independent variables predicted the dependent variable or not. The findings revealed that the independent variables (inclusive early childhood education, play and recreational activities) were associated and predicted social adjustment of children with hearing impairment in Oyo State, Nigeria. The authors recommended among others that parents should enroll their children in an early childhood education program as part of the early intervention package for the child to help the child start making early interactions with other children in social contexts.
Keywords: Inclusive; early childhood education; play; recreational activities; social adjustment